Effectiveness of Purple Sweet Potato Leaves (Ipomoea batatas L.) in Improving Hemoglobin Levels among Anemic Pregnant Women in the Second and Third Trimesters - Dyah Mayasari Fatwa; Syerina Rusmida; Lilis Nadiah; Lia Anisa; Meita Karina Asiah (Postgraduate, University of Mataram, 2025)
Anemia in pregnancy remains a major public health problem worldwide, contributing to increased maternal and perinatal morbidity and mortality. Purple sweet potato leaves (Ipomoea batatas L.) are rich in iron, folate, vitamin C, and anthocyanins, which are beneficial for hemoglobin synthesis and iron absorption. This study aimed to evaluate the effectiveness of purple sweet potato leaf consumption in increasing hemoglobin levels among pregnant women in the second and third trimesters with anemia. A quasi-experimental study with a pretest–posttest control group design was conducted on 60 pregnant women with anemia (hemoglobin < 11 g/dL). Participants were allocated into an intervention group (n = 30) consuming 100 g of cooked purple sweet potato leaves daily for four weeks, and a control group (n = 30) following the standard antenatal diet without additional intervention. Hemoglobin levels were measured before and after the intervention using the cyanmethemoglobin method. Data were analyzed using the Shapiro–Wilk test, paired t-test, and independent t-test with a significance level of p < 0.05. The mean hemoglobin increase in the intervention group was significantly higher compared with the control group (1.2 ± 0.4 g/dL vs. 0.3 ± 0.3 g/dL; p < 0.001). The between-group mean difference was 0.9 g/dL (95% CI: 0.7–1.1). Daily consumption of purple sweet potato leaves effectively increased hemoglobin levels in pregnant women with anemia during the second and third trimesters. This local food-based intervention may serve as a practical alternative strategy to prevent and manage anemia in pregnancy.